The following result $$ \sum_{k=1}^\infty\left(\psi^{(1)} (k)\right)^2 = 3\zeta(3) $$ where $\psi^{(1)}$ is the polygamma function makes me think there is a nice sum for the series

$$ \sum_{k=1}^\infty \left(\psi^{(1)} (k+a)\right)^2 $$


$$ \sum_{k=1}^\infty \psi^{(1)} (k+a)\psi^{(1)} (k+b) $$

where $a$ and $b$ are any real numbers such that $a >-1, b>-1.$

Could you help me to find it?

  • 2
    $\begingroup$ If one proceeds along the same lines as that result, it seems that all one needs is a general result for the integral $$\int_0^1 \! \!\int_0^1 \frac{u^a v^b \ln u\ln v}{(1-uv)(1 - u)(1-v)}{\rm{d}} u\:{\rm{d}} v.$$ (That, of course, presumes that this integral is tractable...) $\endgroup$ – Semiclassical Aug 3 '14 at 18:24
  • 3
    $\begingroup$ Maybe through the identity: $$\sum_{k=1}^{+\infty}\psi'(k)\, x^k = \frac{x}{6-6x}\left(\pi^2-6\operatorname{Li}_2(x)\right).$$ $\endgroup$ – Jack D'Aurizio Aug 3 '14 at 22:42
  • 5
    $\begingroup$ Based on that Mathematica has suggested that, $$ S_n=\sum_{k=1}^\infty(\psi^{(1)}(k+n))^2 = 3\zeta(3)-\kappa_{n+1} $$ with $\kappa_n$ given by the recurrence $$ \kappa_1=0\\ \kappa_2=\zeta(2)^2\\ \kappa_3=\zeta(2)^2+(\zeta(2)-1)^2\\ \kappa_n=\frac{13 + 2ng_5 + g_3^4 g_2^2 \kappa_{n-3} - g_3^2 g_2^2 (22-16n+3n^2) \kappa_{n-2} + g_3^2 g_2^2 (17-14n+3n^2) \kappa_{n-1}}{g_3^2 g_2^4} $$ where $g_k=(n-k)$. $\endgroup$ – Benedict W. J. Irwin Jun 27 '17 at 15:29
  • 6
    $\begingroup$ This gives $$ S_2=3\zeta(3)-2\zeta(2)^2+2\zeta(2)-1\\ S_3=3\zeta(3)-3\zeta(2)^2+\frac{9}{2}\zeta(2)-\frac{41}{16}\\ S_4=3\zeta(3)-4\zeta(2)^2+\frac{65}{9}\zeta(2)-\frac{2861}{648}\\ S_5=3\zeta(3)-5\zeta(2)^2+\frac{725}{72}\zeta(2)-\frac{133577}{20736}\\ $$ which seem to check out numerically. $\endgroup$ – Benedict W. J. Irwin Jun 27 '17 at 15:29
  • 1
    $\begingroup$ It is not too difficult to show that $$S_n = 3 \zeta(3) - n\zeta(2)^2 +2(nH_{n-1,2} - H_{n-1})\zeta(2) - \sum_{k=1}^{n-1}H_{k,2}^2,$$ where $H_n$ is the $n$-th Harmonic number and $H_{n,2} = \sum_i^n 1/i^2$ $\endgroup$ – Alexander Vlasev Jan 28 '18 at 22:13

We have $$ \int^{1}_{0}\int^{1}_{0}\frac{\log u\log v}{(1-uv)(1-u)(1-v)}dudv=3\zeta(3) $$ Also $$ \int^{1}_{0}\int^{1}_{0}\frac{(uv)^k\log u\log v}{(1-u)(1-v)}dudv=Z(2,k+1)\psi'(k+1)\textrm{, where }Re(k)>-1 $$ The function $Z(s,k)=\sum^{\infty}_{l=0}\frac{1}{(l+k)^s}$ is Hurwitz zeta function. Hence $$ \sum^{a-1}_{k=0}\int^{1}_{0}\int^{1}_{0}\frac{(uv)^k\log u\log v}{(1-u)(1-v)}dudv =\int^{1}_{0}\int^{1}_{0}\frac{(1-(uv)^a)\log u\log v}{(1-uv)(1-u)(1-v)}dudv. $$ Hence $$ \sum^{\infty}_{k=1}\left(\psi'(k+a)\right)^2=\int^{1}_{0}\int^{1}_{0}\frac{(uv)^a\log u \log v}{(1-u v)(1-u)(1-v)}dudv=3\zeta(3)-\sum^{a-1}_{k=0}Z(2,k+1)\psi'(k+1) $$ By trying to generalize the problem we have $$ C_{\nu}=\underbrace{\int^{1}_{0}\ldots\int^{1}_{0}}_{\nu}\frac{\log u_1\ldots \log u_{\nu}du_1\ldots du_{\nu}}{(1-u_1\ldots u_{\nu})(1-u_1)\ldots(1-u_{\nu})}=\sum^{\infty}_{l=0}\left(\int^{1}_{0}\frac{u^l\log u}{1-u}du\right)^{\nu}= $$ $$ =\sum^{\infty}_{l=0}\left(-Z(2,l+1)\right)^{\nu} $$ Also $$ \underbrace{\int^{1}_{0}\ldots\int^{1}_{0}}_{\nu}\frac{u_1^k\ldots u_{\nu}^k \log u_1\ldots\log u_{\nu}du_1\ldots du_{\nu}}{(1-u_1)\ldots (1-u_{\nu})}=(-1)^{\nu}Z(2,k+1)(\psi'(k+1))^{\nu-1} $$ Hence $$ \sum^{a-1}_{k=0}\underbrace{\int^{1}_{0}\ldots\int^{1}_{0}}_{\nu}\frac{u_1^k\ldots u_{\nu}^k \log u_1\ldots\log u_{\nu}du_{1}\ldots du_{\nu}}{(1-u_1)\ldots (1-u_{\nu})}=(-1)^{\nu}\sum^{a-1}_{k=0}Z(2,k+1)(\psi'(k+1))^{\nu-1}= $$ $$ =\underbrace{\int^{1}_{0}\ldots\int^{1}_{0}}_{\nu}\frac{(1-u_1^a\ldots u_{\nu}^a) \log u_1\ldots\log u_{\nu}du_1\ldots du_{\nu}}{(1-u_1\ldots u_{\nu})(1-u_1)\ldots (1-u_{\nu})}. $$ Hence $$ \underbrace{\int^{1}_{0}\ldots\int^{1}_{0}}_{\nu}\frac{(u_1^a\ldots u_{\nu}^a) \log u_1\ldots\log u_{\nu}du_1\ldots du_{\nu}}{(1-u_1\ldots u_{\nu})(1-u_1)\ldots (1-u_{\nu})}=C_{\nu}+(-1)^{\nu-1}\sum^{a-1}_{k=0}Z(2,k+1)(\psi'(k+1))^{\nu-1} $$ And finaly $$ \sum^{\infty}_{k=1}\left(\psi'(k+a)\right)^{\nu}=C_{\nu}+(-1)^{\nu-1}\sum^{a-1}_{k=0}Z(2,k+1)(\psi'(k+1))^{\nu-1} $$

  • $\begingroup$ Thank you very much for your contribution! (+1) I think an interesting case would be a formula for $\sum^{\infty}_{k=1}\left(\psi'(k+a)\right)^{2} $ where $a$ could be any positive real number. $\endgroup$ – Olivier Oloa Nov 25 '18 at 8:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.